NOMOGRAMS TO EVALUATE THE VARIABILITY OF THE SETTING TIME IN EQUIVALENT MORTARS APPLIED IN GUAYAQUIL, ECUADOR (LACCEI, 2024)
In Guayaquil, due to high temperatures, long travel journeys and high-performance expectations, concrete may require up to 6 admixtures. Current methods require up to 5 simulations to determine proper admixture dosage. The aim of this research work is to generate a design tool that determines the setting time according to the dosage of plasticizing and retarding admixtures. In accordance with international, national and company procedures, calorimetric analysis was carried out on 54 scenarios including multiple dosages of cement content, admixtures and water/cement ratio. Based on the evolution of temperature, initial and final setting time was calculated. Additionally, flow and resistance were measured as moderator variables. Therefore, with this information four nomograms were generated. These nomograms present the initial setting time versus the use of plasticizer and retarder, according to the cement content and water/cement ratio. It is concluded that the recommended percentages of additive should be adjusted according to the cement content in the mixture, meaning that high cement content mixtures a lower percentage of admixture will be required, compared to a mixture with low content, to achieve optimal results. It is observed that high plasticizer dosages prolong the setting time without affecting the final strengths. By using nomograms, the volume of concrete waste reduces up to 60%, which benefits economically and environmentally to the company.